Rudolf Bultmanns Begegnung mit dem Judentum: Herrn Eberhard Jüngel zum 70. Geburtstag - Hammann, Konrad (Zeitschrift für Theologie und Kirche, 2005)
R. Bultmann maintained friendships and scholarly relations to Jews and Christians of Jewish descent. During the Third Reich he supported his Jewish friends in various ways. Some Christian theologians reproached him for making statements which contributed to the racial discrimination of the Jews in National Socialism and for interpreting the New Testament in a way which stirred up opinion against the Jews, but the author shows that this criticism was unfounded. Bultmann was in fact strongly opposed to an anti-Jewish interpretation of New Testament texts.